Pemanfaatan Akun Tiktok @infodhaharjogja Sebagai Media Komunikasi Pemasaran Kuliner di Daerah Istimewa Yogyakarta - Ellya Kusuma; Diana Khuntari; Yolanda Presiana Desi (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2024)
TikTok has become a trend in utilizing social media for marketing communication activities. This has become a reason for content creators to create content related to product or service promotion. One of the accounts that uses TikTok as a marketing communication medium is @infodhaharjogja. This account was chosen because after an analysis with website analysis, the engagement rate and comments to the like ratio of @infodhaharjogja were higher compared to other accounts, although the number of its followers was small. This research aims to understand the utilization of the TikTok account @infodhaharjogja as a culinary marketing communication medium in the Special Region of Yogyakarta. The theory underlying this research is the 7C Framework. This research uses a descriptive qualitative method. Data collection was carried out through interviews, observation, and documentation. The results show that the utilization of the TikTok account @infodhaharjogja met five out of seven indicators in the 7C Framework. The indicators that support marketing communication practices are context, content, community, communication, and connection. Context is an aspect to attracts viewers' attention. Content contains valid and interesting information community functions to build interaction among the audience. Communication facilitates active communication between the @infodhaharjogja account and viewers through comments and direct messages. Connection facilitates easy access to information with a single click using hashtags. The two indicators that do not support marketing communication practices are customization and commerce.